Relativistic theory of the double photoionization of heliumlike atoms - Yerokhin, Vladimir; Surzhykov, Andrey (Physical review. A, Atomic, molecular, and optical physics, 2011)
A fully relativistic calculation of the double photoionization of heliumlike atoms is presented. The approach is based on the partial-wave representation of the Dirac continuum states and accounts for the retardation in the electron-electron interaction as well as the higher-order multipoles of the absorbed photon. The electron-electron interaction is taken into account to the leading order of the perturbation theory. The relativistic effects are shown to become prominent already for the medium-Z ions, changing the shape and the asymptotic behavior of the photon energy dependence of the ratio of the double-to-single photoionization cross section.